Structural Price Inertia and Consumption Constraints in Denpasar: Inersia Harga Struktural dan Kendala Konsumsi di Denpasar - Andriani, Ni Luh Ayu Dessy; Setyari, Ni Putu Wiwin (Academia Open, 2026)
General Background The stability of prices is a fundamental prerequisite for sustainable economic development in developing economies, where consumption heavily dictates growth trajectories. Specific Background In dense metropolitan environments characterized by market-based consumption and external supply dependencies, protracted price increases heavily burden budgets and erode resident welfare. Knowledge Gap Most empirical analyses concentrate on national-level monetary transmission and short-term outcomes, neglecting sub-national heterogeneity and the ability of local institutions to mitigate long-term inflationary inertia. Aims This study analyzes monthly time-series data from January 2020 to December 2024 using an Autoregressive Distributed Lag model to evaluate price inertia and the role of local institutional coordination on economic sustainability in a specific municipality. Results The aggregate lagged coefficient reached 0.9714 with a half-life of 24.4 months, indicating highly protracted shocks. While local institutional coordination lowered short-term volatility, external structural rigidities severely constrained long-term stabilization efforts, particularly in highly rigid sectors such as food, housing, and transportation. Novelty This research integrates time-series persistence modeling with regional institutional evaluation to demonstrate that urban price rigidity is fundamentally a structural distribution issue rather than a purely monetary phenomenon. Implications Policymakers must move beyond short-term interventions and prioritize logistical resilience and distribution efficiency to protect economic welfare and ensure sustainable regional development. Highlights The Autoregressive Distributed Lag methodology revealed a protracted adjustment period of twenty-four months following initial macroeconomic shocks. Essential expenditure groups involving food logistics and mobility exhibited severe long-term rigidity. Local institutional coordination successfully mitigated short-term volatility but struggled against external logistical dependencies. Keywords Autoregressive Distributed Lag; Economic Welfare; Price Stability; Regional Development; Supply Chain Resilience